If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6st + -7su + 5sv = 0 Solving 6st + -7su + 5sv = 0 Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Factor out the Greatest Common Factor (GCF), 's'. s(6t + -7u + 5v) = 0Subproblem 1
Set the factor 's' equal to zero and attempt to solve: Simplifying s = 0 Solving s = 0 Move all terms containing s to the left, all other terms to the right. Simplifying s = 0Subproblem 2
Set the factor '(6t + -7u + 5v)' equal to zero and attempt to solve: Simplifying 6t + -7u + 5v = 0 Solving 6t + -7u + 5v = 0 Move all terms containing s to the left, all other terms to the right. Add '-6t' to each side of the equation. 6t + -7u + -6t + 5v = 0 + -6t Reorder the terms: 6t + -6t + -7u + 5v = 0 + -6t Combine like terms: 6t + -6t = 0 0 + -7u + 5v = 0 + -6t -7u + 5v = 0 + -6t Remove the zero: -7u + 5v = -6t Add '7u' to each side of the equation. -7u + 7u + 5v = -6t + 7u Combine like terms: -7u + 7u = 0 0 + 5v = -6t + 7u 5v = -6t + 7u Add '-5v' to each side of the equation. 5v + -5v = -6t + 7u + -5v Combine like terms: 5v + -5v = 0 0 = -6t + 7u + -5v Simplifying 0 = -6t + 7u + -5v The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Solution
s = {0}
| y=11x^2+x+40 | | 3y=-2x+11 | | 2+7x=4x+8 | | ln(10lnx)=4 | | 6a=-18 | | 18p^2-18=77p | | -9+-6y+6y=-9 | | (5x-12)+(3x-2)=180 | | 4p-3q=23 | | j+556=-7 | | 0.21x+252.00=850 | | 6+40=15x-50 | | 4x+70= | | ln(x-1)-ln(x+1)=2 | | 10x+15y=6 | | 0x+15y=6 | | 8d-(2+d)=42 | | 3p+2q=17 | | 8-7+3= | | 34.4*42= | | d-1-15=45 | | -8z-64=72 | | 2(7x+1)=58 | | b-718=115/6 | | 15Y+4=3Y-8 | | b-7-1/8=11-5/6 | | Y=sin^3(4x)cos(4x) | | 1.4*b=b+8 | | 3ab+6= | | -15+2n=73 | | 3(x+5)-6=x-7 | | -3n^2(-2n^5+5n-5)= |